2020
DOI: 10.3390/diagnostics10060414
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of FGF21 and FGF23 as New Biomarkers in Endometrial Cancer Patients

Abstract: Endometrial cancer is one of the most common cancers of the reproductive organ in women. The incidence of it increases from year to year. In our study we assessed role of FGF21 and FGF23 in the diagnostics of patients with endometrial cancer. The study involved 182 patients, who were undergoing abrasion due to perimenopausal bleeding. FGF21, FGF23, and leptin concentration were quantified in serum by multiplex fluorescent bead-based immunoassays (Luminex Corporation). The median of FGF21 protein (181.8 pg/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…FGF21 and FGF23 expression have been implicated in endometrial cancer due to their association with increased expression of leptin (LEP), a hormone produced in adipose tissue. Serum FGF21 and LEP concentrations are increased in patients with endometrial cancer, and associated with low differentiation and higher grade of tumor [ 119 ]. Circulating FGF21 has also been associated with increased risk of CRC [ 118 ].…”
Section: Fgf Signaling Diversity In Cancermentioning
confidence: 99%
“…FGF21 and FGF23 expression have been implicated in endometrial cancer due to their association with increased expression of leptin (LEP), a hormone produced in adipose tissue. Serum FGF21 and LEP concentrations are increased in patients with endometrial cancer, and associated with low differentiation and higher grade of tumor [ 119 ]. Circulating FGF21 has also been associated with increased risk of CRC [ 118 ].…”
Section: Fgf Signaling Diversity In Cancermentioning
confidence: 99%
“…Higher RNA levels of both leptin and leptin receptors were found in prostate cancer patients than in healthy controls in a study including 176 men [ 30 ]. Leptin levels in patients with endometrial cancer were significantly higher than those in the control group [ 31 ].…”
Section: Leptin and Leptin Receptor Expression In Cancermentioning
confidence: 99%
“…In endometrial cancer, no change in the FGF23 plasma concentration is observed ( Cymbaluk-Płoska et al, 2020 ), whereas the FGF23 plasma concentration goes up in advanced-stage epithelial ovarian cancer (EOC) ( Tebben et al, 2005 ), and a defined FGF23 SNP is associated with better prognosis in this tumor entity ( Meng et al, 2014 ). Breast cancer may be associated with oncogenic osteomalacia and raised FGF23 levels ( Savva et al, 2019 ).…”
Section: Fgf23 and Cancermentioning
confidence: 99%